2019
DOI: 10.1108/nfs-05-2018-0150
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of whole oat, especially bran, into a high-fat diet, improves cardio-metabolic risk factors in type 2 diabetic rats

Abstract: Purpose The purpose of this study was to determine the effects of whole oat, oat bran and refined oat incorporation in a high-fat diet (HFD) on cardio-metabolic risk biomarkers in rats with type 2 diabetes mellitus (T2DM). Design/methodology/approach T2DM was induced by feeding male rats with an HFD for 10 weeks, followed by a low dose of streptozotocin. T2DM rats were then divided into four homogeneous groups. Three groups consumed an HFD containing 45 per cent (g/100 g diet) whole oat, oat bran or refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Life style is a major determinant of vitamin D status, and low vitamin D is a health problem, particularly in people of developing countries (Ranasinghe et al, 2018;Syed et al, 2019). Current study revealed the negative effects of HFD-induced obesity against vitamin D status, and therefore, the need for life style modification or diet improvements in preventing the side effects of HFD is further warranted, as previously suggested by Bensalah et al (2018). Previous studies have suggested numerous supplements for improving cardiometabolic risk factors, body weight or oxidative stress markers in animal models (Ani and Aginam, 2018;Mir et al, 2019); however, our study, for the first time, specified the role of vitamin D in improving the inflammatory status in the renal tissue and renal injury in HFDinduced vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 55%
“…Life style is a major determinant of vitamin D status, and low vitamin D is a health problem, particularly in people of developing countries (Ranasinghe et al, 2018;Syed et al, 2019). Current study revealed the negative effects of HFD-induced obesity against vitamin D status, and therefore, the need for life style modification or diet improvements in preventing the side effects of HFD is further warranted, as previously suggested by Bensalah et al (2018). Previous studies have suggested numerous supplements for improving cardiometabolic risk factors, body weight or oxidative stress markers in animal models (Ani and Aginam, 2018;Mir et al, 2019); however, our study, for the first time, specified the role of vitamin D in improving the inflammatory status in the renal tissue and renal injury in HFDinduced vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 55%
“…Evidences have shown that combination of two or more food materials such as cereals and legumes usually increased nutritional properties of the final food products (Tsehayneh et al , 2020). Nutritionally, it is evident that regular intakes of food products that are high in plant bioactive compounds, such as in the present study food formulations, usually prevent diseases such as obesity, diabetes and hypertension (Bensalah et al , 2019; Ardiansyah et al , 2019; Tan et al , 2019).…”
Section: Resultsmentioning
confidence: 72%
“…In oat β-glucan is mainly located in bran and aleurone layers (Demirbas,2005). It is relatively inexpensive oat flour milling by-productand can be added to foods on the assumption that this willcontribute to health benefits (Bensalah et al, 2019,Xue et al, 2020.…”
Section: Introductionmentioning
confidence: 99%